Outcome Predictors in Scrub Typhus Requiring Ventilator and Vasopressor Support - Adhikari, Shital; Poudel, Ramesh Sharma; Shrestha, Shakti; Bhandari, Nisha (Journal of Nepal Health Research Council, 2020)
Background: Age and serum creatinine are known to be predictors of mortality in scrub typhus patients admitted in intensive care unit. This study aimed to explore the factors predicting mortality in patients with scrub typhus requiring both ventilator and vasopressor support in our set up.Methods: A retrospective analysis of 43 patients with scrub typhus (ELISA IgM positive, optical density ?0.5) admitted in Medical Intensive Care unit of Chitwan Medical College Teaching Hospital between April 2016 to September 2017 was performed considering recovery or death (poor outcome) as outcome measurement. Potential variables (p<0.25) from bivariate analysis were used to perform a multivariate logistic regression analysis (p<0.10) to predict mortality. Results: The mortality rate was 56% (24/43). Acute respiratory distress syndrome and shock were observed in all 43 patients. The median (IQR) duration of ventilation use and vasopressor use was 53(101) hours and 48(79.5) hours, respectively. On bivariate analysis, an independent and statistically significant association of mortality with age in years (p=0.039), number of vasopressor use (p<0.001) and serum creatinine more than 1.4 mg/dl (p=0.012) was observed and on multivariate regression analysis, these variables were also the predictors of mortality (age in years: p=0.011, ?=0.115, OR=1.211, 95% CI=1.027-1.225; number of vasopressor use: p=0.009, ?=3.705, OR=40.647, 95% CI=2.532-652.425; serum creatinine more than 1.4 mg/dl: p=0.046, ?=-2.205, OR=0.110, 95% CI=0.013-0.961)Conclusions: In scrub typhus with ARDS and septic shock, increasing age and serum creatinine, and requiring more than one vasopressor to maintain blood pressure are at increased risk of mortality. Keywords: Mortality; predictors; scrub typhus; shock.